Interacting Effects of TSH and Insulin on Human Differentiated Adipocytes - Felske, D.; Gagnon, A.; Sorisky, A. (Hormone and Metabolic Research, 2015)
Subclinical hypothyroidism, characterized by an isolated rise in TSH serum levels with normal thyroid function, is a pro-inflammatory state associated with insulin resistance. Adipocytes express TSH receptors, but it is not known if TSH can directly inhibit insulin signaling. Using primary human differentiated adipocytes, we examined the effects of TSH on insulin-stimulated Akt phosphorylation, and whether conventional PKC (cPKC) were involved. The effect of insulin on TSH-stimulated lipolysis was also investigated. TSH inhibited insulin-stimulated Akt phosphorylation in adipocytes by 54%. TSH activated cPKC, and Gö6976, a PKCα and -β1 inhibitor, prevented the inhibitory effect of TSH on the insulin response. Insulin reduced the ability of TSH to activate cPKC and to stimulate lipolysis.Our data reveal novel interactions between TSH and insulin. TSH inhibits insulin-stimulated Akt signaling in a cPKC-dependent fashion, whereas insulin blocks TSH-stimulated cPKC activity and lipolysis. TSH and insulin act on differentiated human adipocytes to modulate their respective intracellular signals.
Keywords: Akt; protein kinase C; lipolysis